Pembuatan Aplikasi Buku Multimedia Cerita Alkitab - Maggie Mauri Tanuwijaya; Justinus Andjarwirawan; Lily Puspa Dewi (Jurnal Infra, 2017)
Reading is one of the most important functions in life, it is because of every learning process comes from abilities to read. Books with pictures are the books consist of illustrations. For kids, reading a picture book have its own pleasure because they can understand better the content in the book. Bible is hard to understand for kids because there are only words in it. Because of that, a method to explain what is inside the bible for kids should be developed. It will be easier for kids to understand bible if such method exists.Bible Stories Multimedia Book Application is developed in order to help users read, since the stories served in the most interesting way possible using interactive pictures. Steps in the making of this application are: analysis for program planning, program design using use case, activity diagram, flowchart, game scenarios, database system and design interface, and program implementation. This application is developed using HTML, Javascript, PHP, CSS and MySQL database.The examination process showed that this application works fine on Google Chrome and Mozilla Firefox. This Multimedia Book Application provides stories, games, jigsaw puzzle, matching game and sorting game, as shown by questionnaire, 7 of 10 children are able to read and understand bible stories in the early age.